1.6(x+5)-(6.2+0.6x)=-3+2

Simple and best practice solution for 1.6(x+5)-(6.2+0.6x)=-3+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.6(x+5)-(6.2+0.6x)=-3+2 equation:


Simplifying
1.6(x + 5) + -1(6.2 + 0.6x) = -3 + 2

Reorder the terms:
1.6(5 + x) + -1(6.2 + 0.6x) = -3 + 2
(5 * 1.6 + x * 1.6) + -1(6.2 + 0.6x) = -3 + 2
(8 + 1.6x) + -1(6.2 + 0.6x) = -3 + 2
8 + 1.6x + (6.2 * -1 + 0.6x * -1) = -3 + 2
8 + 1.6x + (-6.2 + -0.6x) = -3 + 2

Reorder the terms:
8 + -6.2 + 1.6x + -0.6x = -3 + 2

Combine like terms: 8 + -6.2 = 1.8
1.8 + 1.6x + -0.6x = -3 + 2

Combine like terms: 1.6x + -0.6x = 1x
1.8 + 1x = -3 + 2

Combine like terms: -3 + 2 = -1
1.8 + 1x = -1

Solving
1.8 + 1x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.8' to each side of the equation.
1.8 + -1.8 + 1x = -1 + -1.8

Combine like terms: 1.8 + -1.8 = 0.0
0.0 + 1x = -1 + -1.8
1x = -1 + -1.8

Combine like terms: -1 + -1.8 = -2.8
1x = -2.8

Divide each side by '1'.
x = -2.8

Simplifying
x = -2.8

See similar equations:

| (3-7i)(8+3i)=0 | | 2.96x+3.74=-3.48x-6.15 | | 11d+6=3 | | n-5+7=-4 | | 0.4/-20 | | 4x+9x-8x-5=10 | | 4(-7+x)=5x+(1/4) | | 9x-(5x-9)=5+3x | | 2-17=z/-9 | | -x+4=-20+x | | 3x^2-40x+36=0 | | b+7=7+2b-b | | 8x^2(9x^3-6x+7)= | | -n=-50 | | 4n-2n=16 | | .50(x)-3=-16 | | -3a+6+5a=7a | | Z^2-8z+12= | | 5y+1/4=4y-1/2 | | x/2=4/9 | | .50(x)-3=-14 | | 5/1=m/4 | | .3d-.06+.2d=.4+d | | 35=10+2Q+0.5Q^2 | | 15.3=-7.5k+55.2 | | 4y-6=10y+24 | | .50(x)-3=-8 | | 2x^2+242=0 | | 5m=7/3 | | 14/6=x/15 | | 6v-3+2v=-3 | | N+4n-8-2=20+20n |

Equations solver categories